Disability Studies, Inclusive Pedagogy, and Universal Design for Learning: A Faculty Pilot Experience - Jarman, Michelle; Thompson-Ebanks, Valerie; Singh, Reshmi; Boggs, Christine; Clement, Kristina; Peter, Samantha (Disability Studies Quarterly, 2023)
This essay documents the process of a year-long faculty pilot group in a western U.S. state university that applied disability studies scholarship to collaborative implementation of universal design for learning (UDL) and inclusive practices in teaching. In addition to faculty, library instructors, disabled student representatives, diversity and equity administrators, and disability support staff were involved in this group. The goals were to deepen knowledge about disability history, exclusions, and current innovations from disability communities; to increase knowledge and skills in accessible pedagogies, specifically in UDL; and to expand commitment and community among faculty participants in order to scale up efforts in our institution beyond the pilot group. This essay documents the experiences of the learning group, which consist of an overview of the curricular framework, a discussion of qualitative research from focus group interviews with faculty participants, and insights gained from the process, including unexpected collaborations, community building, and innovative ideas for institutional support and transformation.